Second order sliding mode control scheme for an autonomous underwater vehicle with dynamic region concept - Ismail, Zool Hilmi (Hindawi Publishing Corporation, 2015)
The main goal in developing closed loop control system for an Autonomous Underwater Vehicle (AUV) is to make a robust vehicle from natural and exogenous perturbations such as wind, wave, and ocean currents. However a well-known robust control, for instance, Sliding Mode Controller (SMC), gives a chattering effect and it influences the stability of an AUV. Furthermore, some researchers combined other controls to get better result but it tends to present long computational time and causes large energy consumption. Thus, this paper proposed a Super Twisting Sliding Mode Controller (STSMC) with dynamic region concept for an AUV. STSMC or a second order SMC is adopted as a robust controller which is free from chattering effect. Meanwhile, the implementation of dynamic region is useful to reduce the energy usage. As a result, the proposed controller obtains global asymptotic stability which is validated by using Lyapunov-like function. Moreover, some simulations present the efficiency of proposed controller. In conclusion, STSMC with region based control is effective to be applied for the robust tracking of an AUV. It contributes to give a fast response when handling the perturbations, short computational time, and low energy demand.